Characteristics and outcomes of carbapenemase harbouring carbapenem-resistant Klebsiella spp. bloodstream infections: a multicentre prospective cohort study in an OXA-48 endemic setting - TİGEN, ELİF (My University, 2022)
A prospective, multicentre observational cohort study of carbapenem-resistant Klebsiella spp. (CRK) bloodstream infections was conducted in Turkey from June 2018 to June 2019. One hundred eighty-seven patients were recruited. Single OXA-48-like carbapenemases predominated (75%), followed by OXA-48-like/NDM coproducers (16%). OXA-232 constituted 31% of all OXA-48-like carbapenemases and was mainly carried on ST2096. Thirty-day mortality was 44% overall and 51% for ST2096. In the multivariate cox regression analysis, SOFA score and immunosuppression were significant predictors of 30-day mortality and ST2096 had a non-significant effect. All OXA-48-like producers remained susceptible to ceftazidime-avibactam.
Keywords: Yaşam Bilimleri; Temel Bilimler; Life Sciences; Natural Sciences; BULAŞICI HASTALIKLAR; İmmünoloji; Yaşam Bilimleri (LIFE); Mikrobiyoloji; INFECTIOUS DISEASES; IMMUNOLOGY; Life Sciences (LIFE); MICROBIOLOGY; General Immunology and Microbiology; Immunology; Infectious Diseases; Health Sciences; OXA-48; OXA-232; ST2096; Klebsiella pneumoniae; Ceftazidime-avibactam; PNEUMONIAE; ENTEROBACTERALES; COPRODUCTION; SPREAD; NDM-1; OXA-48; OXA-232; ST2096; Klebsiella pneumoniae; Ceftazidime-avibactam